Habilidades lingüísticas y su impacto en la Lecto - Escritura del subnivel 2 del centro de educación inicial María Angélica Idrovo - Pilaloa Sánchez, Jennifer Tatiana (2023)
Linguistic skills are skills that must be stimulated through the implementation of strategies that help the significant development of spoken and written language. The main objective of this research work is the analysis of linguistic skills and their impact on reading and writing at sublevel 2 of the “María Angélica Idrovo” Initial Education Center. For this reason, the importance of said research work Research lies in the search for different studies that allow the treatment of this problem. Within this research project, non-experimental research design and a qualitative research approach will be used, as well as an explanatory scope. On the other hand, the entire respective composition was analyzed on linguistic skills and the benefits they offer at the time of the development of reading and writing, for which exhaustive research was carried out that was of great importance in developing the proposed topic. Through the observation sheet and the surveys carried out, a precise analysis was achieved. It is worth mentioning that the methods proposed to obtain said data were analytical, synthetic, historical, inductive and deductive research methods, which allowed us to demonstrate the deficiency of said processes within the classroom, for which it is recommended to stimulate . the development of these skills in children so that they are successful in learning to read and write.